The Support System Synergy on Working Productivity From The Perspective of Economic Sharia Law - Farida Nurun Nazah; Saiful Bahri; Dwi Nur Fauziah Ahmad (Indonesian Journal of Law and Policy Studies, 2022)
This study discusses the synergy of support systems on work productivity from the perspective of Islamic economic law. Support system or work productivity support system, is not only interpreted by the quality of human resources, but the whole system that supports each other for the implementation of effective and efficient performance. The research method uses qualitative research that focuses on literature study, including collecting bibliographical sources and processing data or citing references. Support systems that support work productivity include: the quality of human resources, efforts to provide motivation, technological excellence, availability of funds, completeness of facilities, and also infrastructure. Indicators of work productivity will be achieved in the ability to form good work professionalism, increase the results achieved from targets, high morale, self-development in increasing maximum performance, as well as quality as an output of performance results and work efficiency. Work productivity in accordance with Islamic economic law standards is one that reflects Islamic principles and ethics, including: good and useful, diligent at work and able to respect time, doing the best or better, working hard and optimally, competing and helping honest, consistent, has a high sense of belonging to work, responsibility, and is able to grow stronger and more solid human relations.